2015
DOI: 10.5515/jkiees.2015.15.3.151
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sub-chronic Whole-Body Exposure to a 1,950 MHz Electromagnetic Field on the Hippocampus in the Mouse Brain

Abstract: The increasing use of mobile phones has raised public concern about the possible biological effects of radiofrequency electromagnetic field (RF-EMF) exposure on the human brain. To investigate the potential effect of RF-EMF exposure on the brain, we examined the behaviors and hippocampal morphology of C57BL/6 mice after sub-chronic exposure to RF-EMFs with a relatively high SAR level (5.0 W/kg). We applied a 2-hour daily exposure of WCDMA 1,950 MHz using a reverberation chamber that was designed for whole-body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Further, following 7 months of RF-EMF exposure in young adult mice, no changes were observed in protein oxidative damage in mouse brains, indicating that chronic RF-EMF exposure might not induce detrimental effects on young-adult mice [ 46 ]. Additionally, previous reports indicated that RF-EMF did not affect memory or anxiety-related behaviors in either young-adult [ 39 , 45 , 47 ] or aged animals [ 41 , 48 ]. To examine the effects of RF-EMFs on basic locomotor activity, we performed an open field test.…”
Section: Discussionmentioning
confidence: 94%
“…Further, following 7 months of RF-EMF exposure in young adult mice, no changes were observed in protein oxidative damage in mouse brains, indicating that chronic RF-EMF exposure might not induce detrimental effects on young-adult mice [ 46 ]. Additionally, previous reports indicated that RF-EMF did not affect memory or anxiety-related behaviors in either young-adult [ 39 , 45 , 47 ] or aged animals [ 41 , 48 ]. To examine the effects of RF-EMFs on basic locomotor activity, we performed an open field test.…”
Section: Discussionmentioning
confidence: 94%
“…It has been documented that RF‐EMF exposure impaired spatial cognitive function in rats, demonstrating the detrimental effects of RF‐EMF on the central nervous system in laboratory animals (Nittby, Grafström, et al, 2008). Other studies have reported that chronic RF‐EMF exposure did not affect spatial memory on radial‐arm maze or passive avoidance tests (Ammari et al., 2008; Dubreuil, Jay, & Edeline, 2003; Son et al., 2015). However, some beneficial effects were also reported.…”
Section: Introductionmentioning
confidence: 92%